Pengaruh Employer Branding terhadap Turnover Intention Dimediasi Employee Engagement di XYZ Headhunter - Virgi Fahrezi Wibisono; Ni Wayan Mujiati (Mutiara: Multidiciplinary Scientifict Journal, 2023)
Turnover intention is a mental or psychological decision that exists between individual approaches with reference to continuing a job or to leave a job. This turnover can be a clue to the stability of employees in an organization or company, meaning that if the more frequent or higher the turnover rate, the organization can be said to be unstable. Based on the results of a pre-survey conducted by 10 people at Startup XYZ Headhunter, using three statement indicators, the results showed that most respondents showed a desire to leave the company. This study uses employer branding variables as exogenous variables and employee engagement as a mediating variable. Employer branding is a concept of marketing applied in HR management to brand the company into a desirable workplace, while employee engagement is the empowerment of organizational members towards their position and role in the company. This study aims to determine employee engagement in mediating the effect of employer branding on turnover intention at XYZ Headhunter. This research was conducted at XYZ Headhunter with a sample size of 32 respondents using the saturated sampling method. Data collection was carried out using a survey approach, where the research instrument used was a questionnaire. The data collected was then analyzed using path analysis techniques, and the sobel test was used in this study to test the hypothesis of this study. The results and conclusions of this study indicate that employer branding has no effect on turnover intention, employer branding has a positive and significant effect on employee engagement, employee engagement has no effect on turnover intention, and employee engagement does not mediate the effect of employer branding on turnover intention.